2016
DOI: 10.1109/comst.2016.2527741
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Survey of Recent Advancements in Molecular Communication

Abstract: With much advancement in the field of nanotechnology, bioengineering and synthetic biology over the past decade, microscales and nanoscales devices are becoming a reality. Yet the problem of engineering a reliable communication system between tiny devices is still an open problem. At the same time, despite the prevalence of radio communication, there are still areas where traditional electromagnetic waves find it difficult or expensive to reach. Points of interest in industry, cities, and medical applications … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
595
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 839 publications
(625 citation statements)
references
References 244 publications
(303 reference statements)
2
595
0
1
Order By: Relevance
“…It has been shown that the binomial distributed noise can be approximated to a Normal distribution [2]. We add the noise to the molecules counted by the sensor and the results in Fig.…”
Section: B Differentiability and Accuracy Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the binomial distributed noise can be approximated to a Normal distribution [2]. We add the noise to the molecules counted by the sensor and the results in Fig.…”
Section: B Differentiability and Accuracy Resultsmentioning
confidence: 99%
“…INTRODUCTION Molecular communications has gained significant research attention in recent years, providing an alternative and attractive way to communicate at small-scales and in biological environments [1], [2]. Its applications include targeted drug delivery [1], [3], [4] and industrial monitoring [2].…”
mentioning
confidence: 99%
“…Due to the flow may affect the gravity, we denote the final result of gravity as e, the concentration of the molecules which denotes f (t). f (t) can be regarded as the total variation of the concentration at different time t, then we get Equation (3).…”
Section: Impulse Response Of Vertical Channelmentioning
confidence: 99%
“…However, still there are many applications which are not convenient or appropriate for these technologies. For instance, the use of wireless communication inside networks of tunnels, pipelines, or salt water environment, etc., can be very inefficient [2,3]. As another example, with the dimensions of the transmitter and receiver become smaller and smaller, electromagnetic communication is extremely challenging due to constrains such as the ratio of the antenna size to the wavelength of the electromagnetic signal [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is highly appropriate for certain biomedical applications, where the use of electromagnetic (EM) waves is neither possible nor desirable [1]- [2]. In particular, the molecular communication via diffusion (MCvD) is a simple method, which does not require additional infrastructure or external energy.…”
Section: Introduction Molecular Communication (Mc) Is a New Communmentioning
confidence: 99%